ISSUES OF ESTABLISHING THE LEGAL STATUS OF A CIVIL SERVANT - Khojabekov Muftulla Jolmurza Ogli (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article analyzes the legal status of a civil servant, its features, elements and legal consolidation in a separate chapter of the draft Law On Civil Service. However, there are certain shortcomings in the legal regulation of the status of civil servants. In this study, the author attempts to identify the problems of legal regulation of the legal status of civil servants and suggest ways to resolve them. For example, the content and the difference between the concepts of civil servant and civil servant from the point of view of normative content are disclosed. From a practical point of view, it is not the concept itself that is of greatest importance, but the constituents that form it. Traditionally, the legal status of an individual includes rights, freedoms and duties. At the same time, in relation to a civil servant, the range of elements of the legal status is much wider.